Integrative Training of Future Engineers to Innovative Activities in Conditions of Postindustrial Economy - S. V. Yushko; M. F. Galikhanov; V. V. Kondratyev (Высшее образование в России)
The article substantiates the necessity of new priorities and paradigms of innovative engineering activity, changing the role of an engineer and the nature of engineering education. It is demonstrated that the basis of modern technologies is interdisciplinary research that determines the need for integrative training of engineers for innovation. The main characteristics, distinctive features and structure of such activity are given. Based on the qualification levels of future engineers’ and the stages of their professional competencies formation, the requirements for innovative engineers are formulated and a comprehensive approach to the formation of engineering competencies is substantiated. The change of the most important trends in the field of engineering training made it possible to update the main provisions of the classical concept of engineering education. The vector of further development of Kazan National Research Technological University as a university center for technological development of the Republicof Tatarstanin the field of chemical technologies has been outlined.